Red wood Ants (Formica rufa-group) prefer mature pine forests in Variscan granite environments (Hymenoptera: Formicidae) - Berberich, Gabriele M.; Berberich, Martin B.; Gibhardt, Matthias (Fragmenta entomologica, 2022)
We used presence/absence data of 5,160 red wood ant nests (RWA; Formica polyctena) acquired in a systematic large-scale area-wide survey in two study areas (≈350 ha) in the Oberpfalz, NE Bavaria, Germany to explore for the first time the influence of variable (e.g., forest type, tree age) and quasi-invariant factors (e.g., tectonics, geochemical composition of the bedrock) on nest size and spatial distribution for Variscan granites. A combination of the forest type (mature pine-dominated forests (≈80–140 years) as main variable factor and the geochemical property of the Variscan granites with their high natural Radon potential and moderate heat production as main quasi-invariant factor could explain the high nest numbers in both study areas. In addition, the spatially clustered distribution patterns of the observed nests suggest a strong interaction between nests and their quasi-invariant environment, especially the directionality of the present-day stress field and the direction of the tectonically formed “Erbendorfer Line”. In general, such a combination of variable and quasi-invariant factors can be addressed as particularly favorable RWA habitats.